Divergent sequences of tetraspanins enable plants to specifically recognize microbe-derived extracellular vesicles - Jinyi Zhu; Qian Qiao; Yujing Sun; Yuanpeng Xu; Haidong Shu; Zhichao Zhang; Fan Liu; Haonan Wang; Wenwu Ye; Suomeng Dong; Yan Wang; Zhenchuan Ma; et al. (Nature Communications, 2023)
Abstract Extracellular vesicles (EVs) are important for cell-to-cell communication in animals. EVs also play important roles in plant–microbe interactions, but the underlying mechanisms remain elusive. Here, proteomic analyses of EVs from the soybean (Glycine max) root rot pathogen Phytophthora sojae identify the tetraspanin family proteins PsTET1 and PsTET3, which are recognized by Nicotiana benthamiana to trigger plant immune responses. Both proteins are required for the full virulence of P. sojae. The large extracellular loop (EC2) of PsTET3 is the key region recognized by N. benthamiana and soybean cells in a plant receptor-like kinase NbSERK3a/b dependent manner. TET proteins from oomycete and fungal plant pathogens are recognized by N. benthamiana thus inducing immune responses, whereas plant-derived TET proteins are not due to the sequence divergence of sixteen amino acids at the C-terminal of EC2. This feature allows plants to distinguish self and non-self EVs to trigger active defense responses against pathogenic eukaryotes.